2022
DOI: 10.1021/acsaem.2c02575
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum-Single Atom Catalyst for High-Efficiency Cobalt(III)/(II)-Mediated Hybrid Photovoltaics

Abstract: The exploration of catalysts with remarkable activity and good stability toward the Co2+/3+(bpy)3 redox reaction is highly desirable for hybrid photovoltaics. In this study, Mo-single-atom catalysts have been successfully synthesized through a facile “embedding–sintering–etching” approach. The as-obtained Mo- single-atom catalysts (SACs) featured the coordination of each Mo-single atom with four nitrogen atoms (Mo1–N4) within the nitrogen-doped carbon (N–C) support, which was verified by X-ray absorption fine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…[6][7][8][9][10] The power conversion efficiency (PCE) of DSSCs can be maximized by optimizing the dye-sensitized TiO 2 photoanode, electrolyte containing a redox couple (such as I 3 − /I − , Co 2+ / 3+ (bpy) 3 ), and counter electrode (CE). [11][12][13][14][15] From the perspective of redu-cing cost and achieving a satisfactory PCE, developing costeffective CE catalysts is indispensable as the main function of the CE is to collect electrons from the external circuit and then catalyse I 3 − to I − . [16][17][18] Although enormous efforts have been made to improve the activity of catalysts for future large-scale application, appropriate materials with excellent catalytic activity, fast charge-transfer capability, and satisfactory electrochemical stability are still needed for design by a mature and reliable strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] The power conversion efficiency (PCE) of DSSCs can be maximized by optimizing the dye-sensitized TiO 2 photoanode, electrolyte containing a redox couple (such as I 3 − /I − , Co 2+ / 3+ (bpy) 3 ), and counter electrode (CE). [11][12][13][14][15] From the perspective of redu-cing cost and achieving a satisfactory PCE, developing costeffective CE catalysts is indispensable as the main function of the CE is to collect electrons from the external circuit and then catalyse I 3 − to I − . [16][17][18] Although enormous efforts have been made to improve the activity of catalysts for future large-scale application, appropriate materials with excellent catalytic activity, fast charge-transfer capability, and satisfactory electrochemical stability are still needed for design by a mature and reliable strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional catalysts, single-atom catalysts (SACs) have exhibited the huge potential advantages of catalytic properties toward various reactions stemming from the unique metal coordination environment and special electronic structure. The atomically dispersed characteristics of SACs always involve the strong interactions between central metal atoms and coordination species on the support. Their inherently atomic configurations originating from metal–support interactions strongly influence the catalytic behaviors toward various types of reactions . Previous studies have demonstrated that the enhanced catalytic performance could be ascribed to the strong interactions and considerable charge transfer between the central metal atoms and coordination species. The representative merits of SACs are distinguished from that of traditional nanocatalysts. Enlightened by the above-mentioned findings, SACs could be explored finely as ideal catalysts for SRR in QD photovoltaics.…”
mentioning
confidence: 99%
“…[11][12][13] However, Platinum reserves are limited and expensive, severely inhibiting large-scale commercial applications. [14][15][16][17][18] Therefore, it is important to explore a simple yet controllable method to alternative Pt CE for DSSCs.…”
mentioning
confidence: 99%